A neuropsychological study of active amateur boxers. Issue 8 (August 1987) - Brooks, N; Kupshik, G; Wilson, L; Galbraith, S; Ward, R
Abstract : Neuropsychological examinations were carried out on 29 amateur boxers and 19 controls matched for age, ethnicity, and education. There was no evidence of significantly impaired performance in the boxers. Within the boxing group, a variety of features of boxing history were examined as possible predictors of cognitive performance (such as number of knockouts, duration of boxing). No feature was a significant predictor of lower cognitive performance.